2017
DOI: 10.1007/s00383-017-4128-x
|View full text |Cite
|
Sign up to set email alerts
|

How long will I have my ACE? The natural history of the antegrade continence enema stoma in idiopathic constipation

Abstract: The ACE survival curve estimates the proportion of patients with idiopathic constipation who can expect closure (either due to success or failure) at certain timepoints. This may be useful for patient counseling. Younger age at ACE was associated with earlier closure (for success).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…In addition to improvement with current symptoms, over one‐third of patients in our sample were able to bridge from ACE therapy to laxative therapy. This matches similar numbers in the nonsyndromic population, suggesting a benefit to both short‐term and long‐term outcomes from ACE therapy in these patients 24 …”
Section: Discussionsupporting
confidence: 78%
“…In addition to improvement with current symptoms, over one‐third of patients in our sample were able to bridge from ACE therapy to laxative therapy. This matches similar numbers in the nonsyndromic population, suggesting a benefit to both short‐term and long‐term outcomes from ACE therapy in these patients 24 …”
Section: Discussionsupporting
confidence: 78%
“…18,32 The reason for the mixed findings across results may be that both younger age and older age are associated with negative outcomes. Khoo et al 41 suggest there may be an optimum age for ACE between 6 and 12 years old, as younger children may be unable to comply with flushes and toilet sits and teenagers may be given more independence and less supervision with completing flushes (perhaps less than is appropriate) thus leading to less treatment adherence. When considering age as a risk for ACE failure, authors primarily highlighted concerns regarding how age related to adherence.…”
Section: Pre-oper Ative Fac Tor Smentioning
confidence: 99%
“…Several studies found that when full continence was not achieved shortly after procedure, there was a higher chance for disuse of their stomas. 34,37,48 Khoo et al 41 found that patients who had fecal incontinence six weeks after ACE procedure were more likely to have their ACE closed than participants who had achieved continence at six weeks. Mugie et al 42 found that flush regimens that included laxatives were the most effective irrigation solution, and patients who started with an irrigation solution with laxatives were more likely to have success in the long-term.…”
Section: Treatment Adherencementioning
confidence: 99%
“…This suggests that colonic dysmotility may not only contribute to the etiology of FC but may also be a consequence of long-standing FC, possibly because of fecal stasis leading to suboptimal colonic motor function. 10,[13][14][15][16][17][18] Sacral Nerve Stimulation Sacral nerve stimulation (SNS) involves low-amplitude electrical stimulation of the sacral nerves. This effect can be administered via transcutaneous stimulation of the posterior tibial nerve, transabdominal stimulation, or via an electrode placed through the sacral foramen.…”
Section: Ileostomymentioning
confidence: 99%
“…or after successful antegrade irrigation. [13][14][15][16][17][18] Another factor which is under debate is whether antegrade access should accompany the resection, which may help with emptying in the short term before retrying the colon on a medical regimen. 36 There are still many reports describing major procedures to treat FC with "failure of medical management" in patients for whom an ACE was not tried first.…”
Section: Colonic Resectionmentioning
confidence: 99%